+0  
 
0
72
2
avatar

Let f(x)=Ax+B and g(x)=Bx+A, where A≠B. If f(g(x)) - g(f(x)) = B - A, what is A+B?

 Mar 26, 2020
 #1
avatar+154 
+1

Phill plz help me out i have an urgent questions plz if you have time

 Mar 26, 2020
 #2
avatar+111330 
+2

f (g(x))   =  A[ Bx + A]  + B  =  ABx + A^2  + B

 

g(f(x))  =  B[ Ax + B ]  + A =   ABx +B^2  + A

 

So

 

[  f(g(x)  - g(f(x))  ]  =   B   -  A

 

[  ( ABx  + A^2  + B )  -  (ABx  + B^2 + A) ]    = B   -  A

 

  A^2  + B   - B^2  - A  =  B  - A

 

A^2 - B^2    +  B -  A   =  B   - A

 

A^2 - B^2  =  0

 

(A + B)  ( A - B)  =  0

 

A + B  =  0       

 

 

cool cool cool

 Mar 26, 2020

11 Online Users